2014
DOI: 10.18056/seci2014.1
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Pain Management Using the WHO Analgesic Ladder in Children with Cancer in South Egypt Cancer Institute, Assiut University

Abstract: Background: The 2012 WHO guidelines recently recommended the 2step strategy in managing pediatric cancer pain. There is little experimental evidence to support this practice. Objectives: To describe characteristics & causes of pain in department of pediatric oncology in South Egypt Cancer Institute, to ascertain the effectiveness of WHO analgesic ladder in these pediatric cancer patients & to address side-effects occurred under treatment with opioid therapy in accordance with step 2 & 3 of the ladder. Methods:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
(4 reference statements)
2
0
0
Order By: Relevance
“…Our findings are more or less comparable with those of Niscola et al 18 whose study, yet involving adults with hematologic cancer, revealed that, for a total number of 223, pathophysiology was as follows:103 (46%) deep somatic, deriving from bone in most cases, 44 (20%) superficial somatic (mucositis and cutis derangements), 40 (18%) visceral, 12 (5%) neuropathic, 24 (11%) mixed or due to unknown mechanisms. 15 Also, our results were similar to those reported by Abdel˗Hadi et al 19 whose study, which was involving pediatric cancer patients revealed that, out of 133 pain cycles, 'Somatic' pain was the most frequent type, constituting (77.4%), followed by 'Visceral' type in (16.5%), and 'Neuropathic' type in (6.0%) of pain cycles. 19 Moreover, we observed that somatic pain was most frequently associated with leukemias, while visceral pain was most frequently associated with lymphomas (P value < 0.0005) (Figure 4,8 & Table 1).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our findings are more or less comparable with those of Niscola et al 18 whose study, yet involving adults with hematologic cancer, revealed that, for a total number of 223, pathophysiology was as follows:103 (46%) deep somatic, deriving from bone in most cases, 44 (20%) superficial somatic (mucositis and cutis derangements), 40 (18%) visceral, 12 (5%) neuropathic, 24 (11%) mixed or due to unknown mechanisms. 15 Also, our results were similar to those reported by Abdel˗Hadi et al 19 whose study, which was involving pediatric cancer patients revealed that, out of 133 pain cycles, 'Somatic' pain was the most frequent type, constituting (77.4%), followed by 'Visceral' type in (16.5%), and 'Neuropathic' type in (6.0%) of pain cycles. 19 Moreover, we observed that somatic pain was most frequently associated with leukemias, while visceral pain was most frequently associated with lymphomas (P value < 0.0005) (Figure 4,8 & Table 1).…”
Section: Discussionsupporting
confidence: 91%
“…15 Also, our results were similar to those reported by Abdel˗Hadi et al 19 whose study, which was involving pediatric cancer patients revealed that, out of 133 pain cycles, 'Somatic' pain was the most frequent type, constituting (77.4%), followed by 'Visceral' type in (16.5%), and 'Neuropathic' type in (6.0%) of pain cycles. 19 Moreover, we observed that somatic pain was most frequently associated with leukemias, while visceral pain was most frequently associated with lymphomas (P value < 0.0005) (Figure 4,8 & Table 1). Another study, dealing with the pain experienced by hospitalized hematologic malignancy adult patients, visceral pain was mostly observed in non˗Hodgkin lymphomas.…”
Section: Discussionsupporting
confidence: 91%